KENDALA EKSISTENSI REZIM: IMPLEMENTASI DJIBOUTI CODE OF CONDUCT DALAM MENANGGULANGI PEROMPAK SOMALIA DI SAMUDERA HINDIA BARAT DAN TELUK ADEN PADA TAHUN 2011 - Swastika, Mayora Bunga; Wahyudi, Fendy Eko; Susetianingsih, Hermini (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2015)
Piracy is an important issue as it is a threat to maritime security.Somali pirate attacks in the Western Indian Ocean and Gulf of Adenare not only disturbing maritime security, but also causing the actuallosses for piracy victims. International Maritime Organizationformed Djibouti Code of Conduct which was signed by twentycountries in the region. Djibouti Code of Conduct has beenimplemented since 29 January 2009. By 2011, the number of somalipirate attacks in the Western Indian Ocean and Gulf of Aden hasincreased from the previous years. Explanative type is used in thisresearch to explain the causes of significant increase in somalipirates attacks when the Djibouti Code of Conduct does exist. Theresult shows there are constraints on Djibouti Code of Conductexistence, namely there is no common interest and the absence ofbenign hegemon.